AaHY5 ChIP-seq based on transient expression system reveals the role of AaWRKY14 in artemisinin biosynthetic gene regulation - Zhou, Limeng (Plant physiology and biochemistry : PPB, 2021)
Copyright © 2021. Published by Elsevier Masson SAS.